Incidence of malignant mesothelioma in Aboriginal people in Western Australia. - Franklin, P.; Reid, A.; Olsen, N.; Peters, S.; de Klerk, N.; Brims, Fraser; Threlfall, T.; Murray, R.; Musk, A. (Wiley-Blackwell Publishing Asia, 2016)
Objectives: To describe the incidence of malignant mesothelioma (MM) in Aboriginal people in Western Australia (WA) and determine the main routes of exposure to asbestos in this population. Methods: All MM cases in Western Australia, as well as the primary source of asbestos exposure, are recorded in the WA Mesothelioma Register. Aboriginal cases up to the end of 2013 were extracted from the register and compared with non-Aboriginal cases with respect to the primary means/source of exposure. Age-standardised incidence rates for each decade from 1980 were calculated for both Aboriginals and non-Aboriginals. Age-standardised mortality rates were calculated for the period 1994–2008 and compared with international rates. Results: There were 39 cases (77% male) of MM among WA Aboriginal people. Twenty-six (67%) were a direct result of the mining of crocidolite at Wittenoom and the subsequent contamination of the surrounding lands. Of the non-Aboriginal MM cases (n = 2070, 86.3% male), fewer than 25% can be attributed to Wittenoom. Aboriginals had consistently higher 10-year incidence rates than non-Aboriginals and, when compared to world populations, the highest mortality rate internationally. Conclusion: When incidence rates in Aboriginal people are compared with non-Aboriginal people, the Wittenoom mining operation has had a disproportionate effect on MM incidence in the local Aboriginal population.